Smart Mompreneur: Digitizing Village Women's MSMEs for Economic Independence and Family Sustainability - Rahma Muti'ah; Mulkan Ritonga; Khairul Rizal (Unram Journal of Community Service, 2025)
Rural women's Micro, Small, and Medium Enterprises (MSMEs) are the pillars of the family economy. However, the management of village MSMEs is still constrained by low product added value, simple product packaging, and a conventional marketing system. This service aims to empower these MSMEs through an innovative mompreneurship approach to achieve economic independence and family sustainability. The implementation method uses participatory training and technical assistance, including four integrative modules: (1) compost fertilizer production for sustainable agriculture; (2) packaging design and standardization; (3) the creation of promotional materials with Canva; and (4) digital marketing and e-commerce strategies. The evaluation results showed a significant increase in participants' competencies, especially in transitioning from traditional to digital marketing. Agricultural products, such as chili, melon, and others, after undergoing quality improvement and branding, have penetrated the modern market through sustainable channels, including local minimarkets and online stores. The "Smart Mompreneur" program is effective in digitizing and increasing the economic value of MSMEs. For sustainability, it is recommended to strengthen joint business groups and provide follow-up assistance. This model can be replicated to support gender equality and inclusive economic growth in line with the SDGs.